A new method of minimum convex hull in computer applications. (1st January 2014) - Liu, Bo; Ruan, Jian
The minimum convex hull is one of the widely studied problems in computational geometry, as well as widely applied in many fields such as in GIS. This paper, through analysis of the disadvantage of the traditional minimum convex hull serial algorithm, puts forward a new method of the minimum convex hull. It introduces three new concepts such as 'absolute vertex', 'absolutely wrong vertex' and 'possible vertex' in minimum convex hull, which can improve the algorithm computing efficiency, and increase the applicability of minimum convex hull in large number of spatial data. In the end, through comparative analysis, compared to the traditional serial algorithm, this paper's algorithm has obvious advantages on seeking minimum convex hull vertex in large number of spatial data, this algorithm execution efficiency is higher than the traditional serial algorithm for minimum convex hull, and it also can improved the applicability of minimum convex hull.